Social Exclusion of Disadvantaged Groups in the Modern Russian Society - Galieva, Evelina Ravilevna; Eflova, Maria Yurievna (Journal of History Culture and Art Research, 2017)
Social exclusion is both a scientific theory and a socio-political discourse. This paper deals with the study of social exclusion of deprived groups such as drug users, which is based on an analysis of complex issues arising from the spread and use of psychoactive substances. The spread of drug abuse as a phenomenon is the cause of the stigmatization of communities and the exclusion of drug users from societies. The problem carriers are not only patients with drug addiction, but also those who have experience of one-time, episodic experiments with drugs and psychotropic substances. This paper is based on the results of empirical studies, which the subject was the study of drug use practices in modern society. The combination of a quantitative and qualitative strategy for data collection and analysis represented a dynamic accumulation of information at different levels about the object under study – social exclusion of drug users: methods of document analysis were applied such as regulatory legal acts, interviews with drug users and experts in the field of drug use and questionnaire survey, as well as secondary analysis of data from all-Russian sociological research. The social exclusion of deprived groups and ways to overcome it directly depend on the nature of the scenarios for social exclusion, which is the result of the stigmatization of deprived groups.